2018
DOI: 10.1021/acs.analchem.8b00885
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Peroxidase-Like Activity of Gold Nanoclusters at Neutral pH for Colorimetric Detection of Heparin and Heparinase Activity

Abstract: The peroxidase-like catalytic activity of gold nanoclusters (Au-NCs) is quite low around physiological pH, which greatly limits their biological applications. Herein, we found heparin can greatly accelerate the peroxidase-like activity of Au-NCs at neutral pH. The catalytic activity of Au-NCs toward the peroxidase substrate 3,3',5,5'-tetramethylbenzidine (TMB) oxidation by HO was 25-fold increased in the presence of heparin at pH 7. The addition of heparin not only accelerated the initial catalytic rate of Au-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(80 citation statements)
references
References 44 publications
3
77
0
Order By: Relevance
“…For example, TMB oxidation implemented by different AuNPs shows an optimum activity at pH values between 3.5 and 4, whereas its optimum temperature is commonly set between 40 and 50 °C ( Fig. 4a) [103][104][105][106][107]. These observations, again, cannot be extrapolated to different peroxidase substrates, i.e., 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) oxidation takes place optimally at lower pH values, while 4-aminoantipyrine (AAP) oxidation is improved at basic pH values [103].…”
Section: Ph and Temperature Dependencementioning
confidence: 99%
“…For example, TMB oxidation implemented by different AuNPs shows an optimum activity at pH values between 3.5 and 4, whereas its optimum temperature is commonly set between 40 and 50 °C ( Fig. 4a) [103][104][105][106][107]. These observations, again, cannot be extrapolated to different peroxidase substrates, i.e., 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) oxidation takes place optimally at lower pH values, while 4-aminoantipyrine (AAP) oxidation is improved at basic pH values [103].…”
Section: Ph and Temperature Dependencementioning
confidence: 99%
“…From the few decades, gold nanoparticles (AuNPs) with intrinsic enzyme‐mimetic activity hold great promise from catalysis to nanomedicine. [ 20–22 ] The previous study has shown that the catalytic properties of AuNPs correspond to the correlation: the smaller the diameter, the more active sites are exposed. [ 22 ] Thus, it is highly expected that ultrasmall AuNPs (UsAuNPs) may possess high enzyme‐mimetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the highest eCL factor values were obtained for 2.5-fold dilution presenting data of 7.6 ± 0.2, 14.4 ± 0.1, 22.2 ± 0.5, 29.8 ± 0.1, and 18.1 ± 0.7 for 2.6, 8, 13, 25, and 38 nm of cross-linked GNPs, respectively. The mechanism behind luminol reaction catalytic activity is attributed to the metal nanoparticles’ surface charge properties [32]. Conventional citrate-reduced GNPs possess a negative charge that electrostatically repulses both anionic luminol and hydroperoxide ions, thus significantly reducing the overall CL signal [16].…”
Section: Resultsmentioning
confidence: 99%